Recensement et cartographie des variétés de cerise dans la région d’Ouled Driss « Souk-Ahras, Algérie » - Benhachich khaoula; Ghuaoui khaoula (My University, 2018)
The municipality of Ouled Driss has experienced during the last four years an important evolution in the agricultural field (arboriculture). The census of cherry varieties in this region has allowed us to identify, by working on four cherry orchards: Moualkia, el Gueria, Zehila 1 and Zehila 2, the different varieties of cherry existing in the region. The morphological and gustatory characteristics of the fruits led us to distinguish the existing varieties in the area of Ouled Driss which are: Bigarreau Moreau, Bigarreau Gros noir, Montmorency cherry, Belle de Chatenay cherry, Napoleon and Vignola. The production of an orchard distribution map has shown the presence of a very extensive area in favor of the development of the arboreal niche, unfortunately until today there are some orchards when counting on the fingers of the hand. ------------------------------------------------------------------------------------------------ شهدت بلدية أولاد إدريس خلال السنوات الأربع الماضية تطوراً هاماً في المجال الزراعي (الأشجار المثمرة). وقد سمح لنا إحصاء أصناف الكرز في هذه المنطقة بالتعرف على أنواع مختلفة منه, الموجودة في المنطقة من خلال العمل على أربعة بساتين للكرز: الموالكية, القارية, زهيلة 1, زهيلة 2. أدت الخصائص المورفولوجية وتذوق الثمار إلى تمييز الأصناف الموجودة في منطقة أولاد إدريس وهي: Bigarreau Moreau, Bigarreau Gros noir, Griotte de Montmorency, Griotte de Belle de Chatenay, Napoléon et Vignola. أظهر إنتاج خريطة توزيع البساتين وجود منطقة واسعة جدًا لصالح تطوير المشتل الشجري. للأسف حتى اليوم هناك بعض البساتين تعد على أصابع اليد. ------------------------------------------------------------------------------------------------